Praktik Media Relations Humas Pemerintah Kabupaten Tanjung Jabung Barat - Mr Eriansyah (Jurnal Komunikasi, 2015)
The importance of media relations for an organization cannot be separated from the "power" that the mass media are not only able to deliver a message to many audiences, but more than that, the basic concept of the media as his stretcher has a function to educate, influence, supervise, inform, entertain, mobilize, and so on. From this strategic media has the potential to provide understanding, raise awareness, change attitudes, opinions, and behaviors as goals to be target institutions. However, it does not mean the media relations officer saw the mass media as a tool. Similarly for the media, news agencies are resources that never dried to be explored. In other words, there is a symbiotic mutualism up between the two that eventually gave birth to a positive image.